Regional differences of COVID-19 pandemic prevention in China: Especially from the perspective of political leaders - Li, Jingli; Zhang, Jianjun; Han, Zhiyong (Frontiers in Public Health, 2022)
Since emergency management capabilities with respect to COVID-19 differ across different regions of China, it is necessary to adopt a more comprehensive perspective to study the reasons for these differences and propose corresponding policies. By investigating 287 prefectural-level administrative regions, this study explores the reasons for different levels of COVID-19 prevention performance. The results lead to the following conclusions. The factors influencing pandemic prevention include both structural factors, such as economic and social factors, and the experiences and characteristics of prefectural-level gov-ernment leaders (party secretaries and mayors), such as grassroots work experience and level of education, which are significantly positively correlated with the progress of pandemic prevention. Based on these findings, we propose suggestions to improve governance capacity in terms of three aspects: the im-provement of emergency management capacity, the appointment of cadres in the context of new chal-lenges and missions, and the establishment collocation of prefectural-level leader teams.